2020
DOI: 10.1186/s12891-020-03515-8
|View full text |Cite
|
Sign up to set email alerts
|

The lateral center-edge angle as radiographic selection criteria for periacetabular osteotomy for developmental dysplasia of the hip in patients aged above 13 years

Abstract: Background This retrospective study sought to delineate the radiographic characteristics of DDH patients over 13 years of age and investigate whether the lateral center-edge angle (LCEA) could serve as radiographic selection criteria for periacetabular osteotomy. Methods We enrolled patients with Hartofilakidis type I DDH without dislocation who underwent periacetabular osteotomy between August 2009 and August 2012. LCEA, anterior central edge angle (ACEA), femoral neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…negative correlation with the LCEA, which is in accordance with previous studies (Werner et al 2012, Zhang et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…negative correlation with the LCEA, which is in accordance with previous studies (Werner et al 2012, Zhang et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The subject pool consisted of 56 adult patients (56 hips) who were diagnosed as DDH according to a comprehensive assessment with the lateral center edge angle [the lateral center edge angle <20° ( Zhang et al, 2020 )], acetabular angle [the acetabular angle >47° ( Fujii et al, 2012 )] and qualitative subluxation estimation, and were scheduled for total hip arthroplasty in our clinic from January 2019 to December 2019. The pool also included 30 healthy subjects with no signs of hip disease who acted as the control group ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Current diagnosis and the severity evaluation mainly rely on the morphologic information, such as the LCEA, the ACEA, the Tönnis angle, and so on, which were provided by medical imaging. It has been reported that the LCEA could be considered as a reliable index because it is closely related to other radiographic markers and is highly associated with cartilage damage and osteoarthritis severity ( Zhang et al, 2020 ). Moreover, it has been extensively used for the clinical diagnosis of DDH.…”
Section: Discussionmentioning
confidence: 99%